A Multidisciplinary Exploratory Approach for Investigating the Experience of Older Adults Attending Hospital Services. (January 2021) - Arakawa Martins, Beatriz; Barrie, Helen; Visvanathan, Renuka; Daniel, Lyrian; Martins, Larissa Arakawa; Ranasinghe, Damith; Wilson, Anne; Soebarto, Veronica
Background: The public areas of the hospital built environment have hardly been investigated for their age-friendliness. Objective: This exploratory, multidisciplinary pilot study investigates the relationship between the physical environment and design of hospital spaces and older people's outpatient experience. Methods: Sixteen participants were recruited from a geriatric Outpatient Clinic at a metropolitan public hospital in Australia. Participants were engaged in a concurrent mixed-method approach, comprising a comprehensive geriatric survey, walking observation, semi-structured interview and an independent architectural audit. Results: Several elements arising from the hospital environment were identified as facilitators and barriers for its utilization and intrinsically related to participants' physical capacity. Discussion: Age-friendly hospital design needs to consider strategies to remove barriers for older adults of different capacities, thus promoting healthy aging.